Affects deposition time and substrate temperature on optical properties of ZnO thin film - Pogrebnyak, A.D.; Jameel, N.Y.; Mommed, G.A-K.M. (Физическая инженерия поверхности, 2011)
ZnO thin films have been prepared with different processes such as pulsed-laser deposition, chemical vapor deposition spray pyrolysis and sol-gel process etc. Among them, chemical vapor deposition (CVD), in this paper we will study the effect of, deposition time and temperature of the substrates. The temperatures of substrate was varied as was the deposition time of ZnO in order to determine the best substrate temperature and deposition time to produce the best physical properties of deposition.
using pure zinc acetate hydrous Zn(Ch₃COO)₂⋅2H₂0 with 98% purity. The best deposition time was found to be (20 min) while the best temperature degree was (500 °C). ZnO тонких плівок були підготовлені з різними процесами, такими як імпульсного лазерного осадження, хімічного осадження парів ПІРОЛІЗ і золь-гель процесу і т.д. Серед них, хімічне осадження парів (CVD), в цій статті ми будемо вивчати вплив, час осадження і температури підкладки. Температура підкладки варіювалася як було часу осадження з ZnO з метою визначення кращих температур підкладки та осадження час, щоб зробити найкращі фізичні властивості осадження, з використанням чистого цинку ацетат водний Zn(Ch₃COO)₂⋅2H₂ з 98% чистоти. Кращий час осадження виявиться (20 хв), а найкраща температура мірою була (500 °С). ZnO тонких пленок были подготовлены с различными процессами, такими как импульсного лазерного осаждения, химического осаждения паров ПИРОЛИЗОМ и золь-гель процесса и т.д. Среди них, химическое осаждение паров (CVD), в этой статье мы будем изучать влияние, время осаждения и температуры подложки. Температура подложки варьировалась как было времени осаждения из ZnO с целью определения лучших температуры подложки и осаждения время, чтобы произвести самые лучшие физические свойства осаждения. с использованием
чистого цинка ацетат водный Zn(Ch₃COO)₂⋅2H₂ с 98% чистоты. Лучшее время осаждения оказалось (20 мин), а лучшая температура степени была (500 °С).